NKG2D is a Key Receptor for Recognition of Bladder Cancer Cells by IL-2-Activated NK Cells and BCG Promotes NK Cell Activation - García-Cuesta, Eva María; López-Cobo, Sheila; Álvarez-Maestro, Mario; Esteso, Gloria; Romera-Cárdenas, Gema; Rey, Mercedes; Cassady-Cain, Robin L.; Linares, Ana; Valés-Gómez, Alejandro; Reyburn, Hugh Thomson; Martínez-Piñeiro, Luis; Valés-Gómez, Mar (Frontiers in Immunology, 2015)
Intravesical instillation of bacillus Calmette–Guérin (BCG) is used to treat superficial bladder cancer, either papillary tumors (after transurethral resection) or high-grade flat carcinomas (carcinoma in situ), reducing recurrence in about 70% of patients. Initially, BCG was proposed to work through an inflammatory response, mediated by phagocytic uptake of mycobacterial antigens and cytokine release. More recently, other immune effectors such as monocytes, natural killer (NK), and NKT cells have been suggested to play a role in this immune response. Here, we provide a comprehensive study of multiple bladder cancer cell lines as putative targets for immune cells and evaluated their recognition by NK cells in the presence and absence of BCG. We describe that different bladder cancer cells can express multiple activating and inhibitory ligands for NK cells. Recognition of bladder cancer cells depended mainly on NKG2D, with a contribution from NKp46. Surprisingly, exposure to BCG did not affect the immune phenotype of bladder cells nor increased NK cell recognition of purified IL-2-activated cell lines. However, NK cells were activated efficiently when BCG was included in mixed lymphocyte cultures, suggesting that NK activation after mycobacteria treatment requires the collaboration of various immune cells. We also analyzed the percentage of NK cells in peripheral blood of a cohort of bladder cancer patients treated with BCG. The total numbers of NK cells did not vary during treatment, indicating that a more detailed study of NK cell activation in the tumor site will be required to evaluate the response in each patient.